Holocene vegetation dynamics and inferred climate changes at Svanavatnet, Mo i Rana, northern Norway - Bjune, AE; Birks, HJB (BLACKWELL PUBLISHING, 2008)
Pollen and plant macrofossil analyses from Svanavatnet in northern Norway provide records of past vegetation and climate in this region from c. 8700 cal.yr BP until the present. Pollen accumulation rates and the presence of plant macrofossils indicate that Betula pubescens (birch) was present from c. 8600 cal.yr BP and Pinus sylvestris (pine) from c. 8200 cal.yr BP. Quantitative climate is reconstructed using modern pollen-climate transfer functions based on weighted-averaging partial least squares regression. A rapid increase in mean July temperature (T-jul) and mean annual precipitation (P-ann) is inferred for the early Holocene. At times when tree abundance is at its highest and most diverse, inferred Tjul indicates maximum temperatures during the mid-Holocene of about 2 degrees C warmer than at present. During the same time period, inferred Pann is 200 - 300mm above present-day conditions until c. 3000 cal.yr BP. Mean January temperatures (T-jan) are reconstructed to be about 2 degrees C warmer than today from 8000 to 3500 cal.yr BP. After 3500 cal.yr BP until today, a gradual decrease is seen in all the reconstructed climate parameters, together with a reduction in tree abundance and the development of a mosaic of open vegetation with grasses, dwarf shrubs and wet areas, and of woodland containing B. pubescens, P. sylvestris and Picea abies (spruce).